Selective inhibition of miR-21 by phage display screened peptide - Bose, Debojit; Nahar, Smita; Rai, Manish Kumar; Ray, Arjun; Chakraborty, Kausik; Maiti, Souvik (Nucleic Acids Research, 2015)
miRNAs are nodal regulators of gene expression and deregulation of miRNAs is causally associated with different diseases, including cancer. Modulation of miRNA expression is thus of therapeutic importance. Small molecules are currently being explored for their potential to downregulate miRNAs. Peptides have shown to have better potency and selectivity toward their targets but their potential in targeting and modulating miRNAs remain unexplored. Herein, using phage display we found a very selective peptide against pre-miR-21. Interestingly, the peptide has the potential to downregulate miR-21, by binding to pre-miR-21 and hindering Dicer processing. It is selective towards miR-21 inside the cell. By antagonising miR-21 function, the peptide is able to increase the expression of its target proteins and thereby increase apoptosis and suppress cell proliferation, invasion and migration. This peptide can further be explored for its anti-cancer activity in vivo and may be even extended to clinical studies.

Distinct metabolic states of a cell guide alternate fates of mutational buffering through altered proteostasis - Verma, Kanika; Saxena, Kanika; Donaka, Rajashekar; Chaphalkar, Aseem; Rai, Manish Kumar; Shukla, Anurag; Zaidi, Zainab; Dandage, Rohan; Shanmugam, Dhanasekaran; Chakraborty, Kausik (Nature Communications, 2020)
Metabolic changes alter the cellular milieu; can this also change intracellular protein folding? Since proteostasis can modulate mutational buffering, if change in metabolism has the ability to change protein folding, arguably, it should also alter mutational buffering. Here we find that altered cellular metabolic states in E. coli buffer distinct mutations on model proteins. Buffered-mutants have folding problems in vivo and are differently chaperoned in different metabolic states. Notably, this assistance is dependent upon the metabolites and not on the increase in canonical chaperone machineries. Being able to reconstitute the folding assistance afforded by metabolites in vitro, we propose that changes in metabolite concentrations have the potential to alter protein folding capacity. Collectively, we unravel that the metabolite pools are bona fide members of proteostasis and aid in mutational buffering. Given the plasticity in cellular metabolism, we posit that metabolic alterations may play an important role in cellular proteostasis.